Treatment of Sarcoma Lung Metastases with Stereotactic Body Radiotherapy. (1st April 2018) - Lindsay, Adam D.; Haupt, Edward E.; Chan, Chung M.; Spiguel, Andre R.; Scarborough, Mark T.; Zlotecki, Robert A.; Gibbs, Parker C.
Abstract : Background . The most common site of sarcoma metastasis is the lung. Surgical resection of pulmonary metastases and chemotherapy are treatment options that have been employed, but many patients are poor candidates for these treatments for multiple host or tumor-related reasons. In this group of patients, radiation might provide a less morbid treatment alternative. We sought to evaluate the efficacy of radiotherapy in the treatment of metastatic sarcoma to the lung. Methods . Stereotactic body radiotherapy (SBRT) was used to treat 117 pulmonary metastases in 44 patients. Patients were followed with serial computed tomography imaging of the chest. The primary endpoint was failure of control of a pulmonary lesion as measured by continued growth. Radiation-associated complications were recorded. Results . The majority of patients (84%) received a total dose of 50 Gy per metastatic nodule utilizing an image-guided SBRT technique. The median interval follow-up was 14.2 months (range 1.6–98.6 months). Overall survival was 82% at two years and 50% at five years. Of 117 metastatic nodules treated, six nodules showed failure of treatment (95% control rate). Twenty patients (27%) developed new metastatic lesions and underwent further SBRT. The side effects of SBRT included transient radiation pneumonitisn = 6, coughn = 2, rib fracturen = 1, chronic painn = 1, dermatitisn = 1, and dyspnean = 1 . Conclusion . Stereotactic body radiotherapy is an effective and safe treatment for the ablation of pulmonary metastasis from sarcoma. Further work is needed to evaluate the optimal role of SBRT relative to surgery or chemotherapy for treatment of metastatic sarcoma.